2005
DOI: 10.1007/s00066-005-1277-y
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric Oxygen and Radiotherapy

Abstract: Recruitment of centers and patients is being strongly encouraged, detailed information is given on www.oxynet.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
72
0
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(77 citation statements)
references
References 48 publications
0
72
0
4
Order By: Relevance
“…In recent years, radiotherapy immediately after HBO has been emerging as an attractive approach for overcoming hypoxia in cancer treatment (Al-Waili et al, 2005;Bennett et al, 2005;Mayer et al, 2005). Several experimental studies have indicated that the elevation in oxygen tension in the tumour is preserved for some time following HBO treatment, thereby allowing the administration of radiotherapy with an improved tumour/normal tissue oxygenation ratio (Kinoshita et al, 2000;Kunugita et al, 2001;Beppu et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, radiotherapy immediately after HBO has been emerging as an attractive approach for overcoming hypoxia in cancer treatment (Al-Waili et al, 2005;Bennett et al, 2005;Mayer et al, 2005). Several experimental studies have indicated that the elevation in oxygen tension in the tumour is preserved for some time following HBO treatment, thereby allowing the administration of radiotherapy with an improved tumour/normal tissue oxygenation ratio (Kinoshita et al, 2000;Kunugita et al, 2001;Beppu et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, clinical studies in patients with gliomas 160 and NSCLC (ref. 161 ) have shown promising results, and several studies with the combination of HBOT and radiotherapy have been also performed 162 . However, this approach is still in its infancy and a number of questions, e.g.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Systematic reviews of HBOT and cancer have described the use of HBOT in patients with malignancy (Daruwalla and Christophi, 2006;Hoggan and Cameron, 2014;Mayer et al, 2005;Moen and Stuhr, 2012). However, several unsolved questions remain connected with HBOT treatment, including severe DNA damage and genetic instability leading to reactivation or augmentation of existing cancer, development of fragile and porous capillaries and associated higher chance of metastasis, initiating aneuplody causing delay in DNA repair of surrounding normal or stromal cells.…”
Section: Abstract: Angiogenesis Chorioallantoic Membrane Hyperbarimentioning
confidence: 99%